2015
DOI: 10.1016/j.bcp.2015.04.009
|View full text |Cite
|
Sign up to set email alerts
|

In vitro studies in a myelogenous leukemia cell line suggest an organized binding of geranylgeranyl diphosphate synthase inhibitors

Abstract: A small set of isoprenoid bisphosphonates ethers have been tested in the K562 chronic myelogenous leukemia cell line to determine their impact on isoprenoid biosynthesis. Five of these compounds inhibit geranylgeranyl diphosphate synthase (GGDPS) with IC50 values below 1 μM in enzyme assays, but in cells their apparent activity is more varied. In particular, the isomeric C-geranyl-O-prenyl and C-prenyl-O-geranyl bisphosphonates are quite different in their activity with the former consistently demonstrating gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Apart from DGBP, Reilly et al tested five more isoprenoid bisphosphonates targeting GGPS while having little or no activity to FDPS, which could disturb the cell viability in the K562 CML cells. 72 Combinations of FDPS and GGPS inhibitors could synergistically inhibit growth and induce apoptosis in leukemia. 73 …”
Section: Agents Targeting Cholesterol Metabolismmentioning
confidence: 99%
“…Apart from DGBP, Reilly et al tested five more isoprenoid bisphosphonates targeting GGPS while having little or no activity to FDPS, which could disturb the cell viability in the K562 CML cells. 72 Combinations of FDPS and GGPS inhibitors could synergistically inhibit growth and induce apoptosis in leukemia. 73 …”
Section: Agents Targeting Cholesterol Metabolismmentioning
confidence: 99%
“…A recent report on the use of lovastatin, zoledronate and digeranylbisphosphonate (Scheme 7) indicated that the simultaneous use of these three compounds as inhibitors of three subsequent steps in geranylgeranyl synthesis led to the inhibition of growth and induction of apoptosis in human chronic myelogenous leukemia cells [142,143]. Scheme (7).…”
Section: Anti-cancer Activitymentioning
confidence: 99%
“…Interestingly, IPP accumulation is less efficient in non-transformed cells than tumor cells with a pharmacologically relevant concentration of ABP ( 45 , 61 ), allowing the immunotherapy for cancer by activating γδ T cells with ABP such as ZOL. Some GTP-binding proteins, such as Ras and Rap1A, are used to indirectly detect the mevalonate pathway blocking and accumulation of intermediates like IPP ( 62 , 63 ). In our study, we proved that ZOL induced accumulation of mevalonate pathway intermediates in osteosarcoma cells, which could be significantly facilitated by VPA.…”
Section: Discussionmentioning
confidence: 99%